Analysis of Antioxidant Activity and Texture Profile of Tender-Young and King Coconut (Cocos nucifera) Mesocarps under Different Treatments and the Possibility to Develop a Food Product - S. Kalina; S. B. Navaratne (International Journal of Food Science)
The present study is aimed at analyzing the antioxidant activity using the free radical 2,2-diphenyl-1-picrylhydrazyl (DPPH) method and the texture using the Brookfield texture analyzer for blanched-solar dried, blanched-cooled with dehumidification, unblanched-solar dried, and unblanched-cooled with dehumidification mesocarps of two varieties of tender coconut, such as King coconut and Young coconut. Under the different treatments, there was a significant difference in the antioxidant activity and texture parameters such as “hardness” and “chewiness” at 5% level of significance. The highest (421.8 ± 12.33 mg/L) and the lowest (856.67±6.72 mg/L) antioxidant activities were recorded for blanched-solar dried mesocarp of King coconut and unblanched-cooled with dehumidification mesocarp of Young coconut, respectively. The texture analysis shows that there is a significant difference in the “hardness” and “chewiness” under different treatments at 5% level of significance. Among the treated mesocarps highest “hardness” value (6619.7±147.1) and “chewiness” value (1079.3±54.90) were recorded for King coconut blanched-solar dried mesocarp and lowest “hardness” value (595.67±36.88) and “chewiness” value (12.634±0.836) were recorded for Young coconut blanched-cooled with dehumidification mesocarp. Since the blanched-solar dried mesocarp of King Coconut has highest antioxidant activity and lowest “chewiness”, it is more suitable to develop a food product.